2020
DOI: 10.1200/jco.2020.38.15_suppl.4004
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival (OS) and long-term disease-free survival (DFS) of three versus six months of adjuvant (adj) oxaliplatin and fluoropyrimidine-based therapy for patients (pts) with stage III colon cancer (CC): Final results from the IDEA (International Duration Evaluation of Adj chemotherapy) collaboration.

Abstract: 4004 Background: In overall population, IDEA pooled analysis did not demonstrate non-inferiority (NI) regarding 3y DFS in pts with stage III CC receiving 3m vs. 6m of adj FOLFOX/CAPOX. However, in pts treated with CAPOX (especially in low-risk pts), 3m of therapy was as effective as 6m. Results of OS and 5y DFS are reported. Methods: OS was defined as time from enrollment to death due to all causes. OS NI margin was conservatively set to be Hazard Ratio (HR) = 1.11, which is equivalent to: the maximum accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 0 publications
2
34
0
2
Order By: Relevance
“…The 5-year OS was not significantly different between 3 months (82.4%) and 6 months of treatment (82.8%) in the whole population (HR:1.02, 95%CI 0.95-1.11). Interestingly, for high-risk stage III patients treated with CAPOX, the absolute difference in 5-year OS rate between 3 and 6 months was only 1% (71.4% versus 72.4%, respectively) with an HR of 1.02 (95%CI 0.89-1.20), while for those treated with FOLFOX, the absolute difference in 5-year OS rate was 2.8% between the two treatment durations (72.5% versus 75.3%) with a HR of 1.12 (95%CI 0.98-1.27) [33].…”
Section: Duration Of Adjuvant Chemotherapy: Idea Collaborationmentioning
confidence: 93%
“…The 5-year OS was not significantly different between 3 months (82.4%) and 6 months of treatment (82.8%) in the whole population (HR:1.02, 95%CI 0.95-1.11). Interestingly, for high-risk stage III patients treated with CAPOX, the absolute difference in 5-year OS rate between 3 and 6 months was only 1% (71.4% versus 72.4%, respectively) with an HR of 1.02 (95%CI 0.89-1.20), while for those treated with FOLFOX, the absolute difference in 5-year OS rate was 2.8% between the two treatment durations (72.5% versus 75.3%) with a HR of 1.12 (95%CI 0.98-1.27) [33].…”
Section: Duration Of Adjuvant Chemotherapy: Idea Collaborationmentioning
confidence: 93%
“…Interestingly, the risk of early recurrence in patients with RDI-O < 60% concerned especially low-risk group. These results should be referred to the abovementioned IDEA project and CAPOX e cacy in low-risk group [20][21][22]. It seems, that RDI-O may be a more accurate re ection of the true patient-relevant bene t of adjuvant chemotherapy among stage III CC.…”
Section: Discussionmentioning
confidence: 87%
“…Tsai et al have shown that at least eight FOLFOX cycles are needed to have OS bene t, and seven to ensure DFS [19]. Moreover, in the International Duration Evaluation of Adjuvant Therapy (IDEA) project in stage III CC patients, the noninferiority of FOLFOX/CAPOX regimens used for 3 vs. 6 months was not demonstrated [20][21][22]. Although in the lower risk group (pT1-3/N1), the 3-month (4 cycles) CAPOX was as effective as the 6-month (8 cycles) treatment and the 3-year rate of DFS was 74.6% and 75.5%, respectively [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Tsai et al have shown that at least eight FOLFOX cycles are needed to have OS bene t, and seven to ensure DFS [19]. Moreover, in the International Duration Evaluation of Adjuvant Therapy (IDEA) project in stage III CC patients, the noninferiority of FOLFOX/CAPOX regimens used for 3 vs. 6 months was not demonstrated [20][21][22]. However, in the lower risk group (pT1-3/N1), the 3-month (4 cycles) CAPOX was as effective as the 6-month (8 cycles) treatment and the 3-year rate of DFS was 74.6% and 75.5%, respectively [20][21][22].…”
Section: Discussionmentioning
confidence: 99%